Development and optimization of Curcuma longa Linn. oleoresin non-aqueous gel for transdermal delivery - Dewa Ayu Arimurni; Made Dwi Pradipta Wahyudi S; Erika Yuda Colatama (Universitas Ahmad Dahlan, 2022)
A long-term oral administration of NSAID and DMARD on rheumatoid arthritis (RA) treatment may cause gastritis, kidney, and cardiovascular disorder. One of the alternative therapies that have been investigated is by using herbal medicine such as Curcuma longa Linn. which contains curcumin and essential oils. Even though both compounds are quite effective in treating RA, poor aqueous solubility and low intestinal absorption limit their oral bioavailability. To overcome these drawbacks, transdermal delivery was chosen as an alternative route of administration. This study was aimed to formulate the Curcuma longa Linn. oleoresin into a transdermal non-aqueous gel system using Carbopol 934 and low substituted hydroxypropyl cellulose (4.25:0.75 %) as the gelling agent. In this study, multiple solvents (PEG 400, PG, glycerin, ethanol, and tween 20) were used in the system. The solvents were chosen based on their ability to dissolve the gelling agents. Optimization was done using a simplex lattice design based on the physical characteristics (viscosity, pH, spreadability, and adhesivity) of the prepared gel. The system with the optimum concentration of PEG 400 and PG was then observed for its stability and in vitro transport through snakeskin membrane using Franz diffusion cell with PBS pH 7.4 as acceptor medium. The optimal formula was comprised of 75% PEG and 25% PG which has a viscosity of 6.34+0.19 dPa.s, adhesivity of 6.05+0.11 seconds, pH of 5.16+0.09, spreadability of 6.94+0.06 cm, and quite stable after freeze-thaw cycling test, whilst around 26.85% curcumin was diffused through the membrane (flux = 0.084 mg.cm-2) after 2 hours. It can be concluded that the Curcuma longa Linn. oleoresin can be formulated into a non-aqueous gel system, which showed a fair gel physical characteristic with good stability and ability to permeate across the skin membrane, and is promising to be further developed as an alternative for RA treatment.